PERSEPSI AKUNTAN PUBLIK TERHADAP AKUNTABILITAS KEUANGAN PARTAI POLITIK PADA KANTOR AKUNTAN PUBLIK DI MALANG - Rachmawati, Ike (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
This study entitled "Perceptions of Political Parties and Financial Accountability Campaign Funds by Public Accountant" with the aim of the research to find out if there were no differences in the perception of public accounting and financial accountability of political party campaign funds. Data collection methods used in this study is to use surveys in which sample collection through questionnaires. Researchers took the object of research in public accounting firm located in the city of Malang, a sample number of 33 respondents. The analysis used in this research is descriptive analysis with the help of the computer program SPSS (Statistical Package For Social Science) version 11. Sampling techniques are used to using the method judgemen / purposive sampling, the researcher uses a specific consideration of the elements are selected as the sample population. Tests are conducted to answer the researchers' hypothesis using one sample t test trials. The first hypothesis testing results show that the sig. (2-tailed) 0.05 then H1 is received and Ho is rejected, this shows that the hypothesis is accepted which means the researchers found no differences in the perception of public accountants of the financial accountability of political parties, while the second hypothesis test results showed the sig. (2-tailed) 0.05 then the H1 accepted and rejected Ho ang means there is no difference in the perception of public accountants to the accountability of campaign funds.The conclusion from this study that there is no difference in perception of the public accountant and financial accountability of political party campaign funds. Suggestions are given for further research investigator of the study population are expected not only to the public accounting firm in the city of Malang, but is extended to the public accounting firm on the outskirts of Malang and increase the number of variables with the variable political party financial reports and financial statements of a political party after the audit so that the bias comparison between the results of audit visits to the perception of public accountants.